Using neural networks to integrate structural analysis package and optimization package. Issue 3 (April 2016) - Kao, Chin-Sheng; Yeh, I-Cheng
Abstract To solve structural optimization problems, it is necessary to integrate a structural analysis package and an optimization package. Since most structural analysis packages suffer from closeness of system, it is very difficult to integrate it with an optimization package. To overcome the difficulty, we propose a possible alternative, DAMDO, which integrate Design, Analysis, Modeling, Definition, and Optimization phases into an integration environment as follows. (1)Design first generate many possible structural design alternatives. Each design alternative consists of many design variablesX . (2)Analysis employ the structural analysis software to analyze all structural design alternatives to obtain their internal forces and displacements. They are the response variablesY . (3)Modeling employ artificial neural networks to build modelY  = f (X ) to obtain the relationship functions between the design variablesX and the response variablesY . (4)Definition employ the design variablesX and the response variablesY to define the objective function and constraint functions. (5)Optimization employ the optimization software to solve the optimization problem consisting of the objective function and the constraint functions to produce the optimum design variablesX *. Optimization of truss structures was used to validate the DAMDO approach. The empirical results show that the truss optimization problems can be solved by the DAMDO approach, which employ neural networks to integrate the structural analysis package and optimization package without requiring direct integration of the two packages. This approach is promising in many engineering optimization domains which need to couple an analysis package and an optimization one to obtain the optimum solutions.